Free Time Culture in a Networked Society - M. Voronova, Elena; P. Andreeva, Marina; Yu. Tumanov, Dmitriy; Thanh Nguyen, Phong; Le Hoang ThuyTo Nguyen, Quyen (International Journal of Psychosocial Rehabilitation, 2024)
The article reflects the importance of analyzing the development of a leisure culture, which should be carried out on the basis of theoretical reflection and methodological development of new approaches to the study of culture and the cultural formation of personality in modern society. The purpose of the work is to consider the features of the formation and transformation of a free time culture in a network society. The scientific novelty of the work lies in the consideration of the concept of “downshifting” in the sphere of free time culture, as well as in the analysis of the actual results of empirical sociological research in the context of changing leisure practices in reflecting age, regional and other differences in the studied indicators. The authors also drew attention to the fact that human interaction with culture is never completely harmonious and all-encompassing. It is emphasized that the new information culture gives leisure certain stable forms of functioning. The concept of "virtual" becomes a key in the organization of modern society. It has been shown that an important social phenomenon in the life of modern youth has become new types of Internet hobbies: blogging and the Wikipedia web encyclopedia. The importance of the Internet as a means of transmitting and receiving information is noted. Based on the analysis of a representative sociological survey, it was concluded that the Internet is a very popular and attractive means of communication. The problem of Internet addiction as a negative social consequence of the development of the information society is analyzed. The data and conclusions presented in the article can be used by government bodies, educational institutions, youth and other organizations to optimize youth leisure activities.